# If #f(x) = x^2 - x# and #g(x) = 3x + 1# how do you find f(g(x))?

To find ( f(g(x)) ), substitute the function ( g(x) ) into ( f(x) ). So, ( f(g(x)) = f(3x + 1) ). Then, wherever there is an ( x ) in ( f(x) ), replace it with ( 3x + 1 ). Thus, ( f(g(x)) = (3x + 1)^2 - (3x + 1) ). This simplifies to ( f(g(x)) = 9x^2 + 6x + 1 - 3x - 1 ), which further simplifies to ( f(g(x)) = 9x^2 + 3x ).

By signing up, you agree to our Terms of Service and Privacy Policy

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you find the domain of #f(x)=(x^2-4x+4)/(2sin(x))#?
- How do you solve for x?: #e^(-x)+x = 1/3?#
- How do you evaluate the function #f(x)=x^2+1# for f(-3)?
- An attorney charges a fixed fee on $250 for an initial meeting and $150 per hour for all hours worked after that. How do you write an equation in slope-intercept form. Find the charge for 26 hours of work.]?
- What is the domain and range of #y = | x + 3|#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7